Factors Influencing the Language Politeness Behavior of The Z Generation - Pandang, Abdullah; Umar, Nur Fadhilah; Mantasiah, Mantasiah; Arifyadi, Azzam; Amirullah, Muhammad (Bulletin of Counseling and Psychotherapy, 2024)
Language politeness has different standards in every country and even in different regions due to cultural varieties. Thus, factors influencing politeness are also various. The study aims to identify the dominant and pre-dominant factors influencing the language politeness of the Z generation. Nine independent variables were investigated in this study, including gender, school background, discipline, tribe, intensity using social media, intensity adding a comment in social media, semester, and province, as the dependent variables, while the language politeness of the Z gen was the independent variable. The research samples were 1354 students from 3 different provinces, South Sulawesi, Central Sulawesi, and West Sulawesi, selected through random cluster sampling. The instruments in this study included an instrument of factors determining politeness developed by the researchers using a categorization instrument, and Politeness Behavior on Communicating developed using the Likert model. The instrument had been evaluated using EFA and CFA tests, and showed that the model was fit. Data were analyzed using MANOVA continued with the Least of Significant as (LSD). Research findings show four factors influencing language politeness, namely tribe, the intensity of writing comments in social media, provinces, and types of universities. The findings also show that in Indonesia, language politeness is still dominated by factors of culture, religion, and social media. The language politeness of the Z Generation is not only a self-identity in social life but also an image in the virtual world.